Streptomyces antioxidans sp. nov., a Novel Mangrove Soil Actinobacterium with Antioxidative and Neuroprotective Potentials - Ser, Hooi-Leng; Tan, Loh Teng-Hern; Palanisamy, Uma D.; Abd Malek, Sri N.; Yin, Wai-Fong; Chan, Kok-Gan; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2016)
A novel strain, Streptomyces antioxidans MUSC 164T was recovered from mangrove forest soil located at Tanjung Lumpur, Malaysia. The Gram-positive bacterium forms yellowish-white aerial and brilliant greenish yellow substrate mycelium on ISP 2 agar. A polyphasic approach was used to determine the taxonomy status of strain MUSC 164T. The strain showed a spectrum of phylogenetic and chemotaxonomic properties consistent with those of the members of the genus Streptomyces. The cell wall peptidoglycan was determined to contain LL-diaminopimelic acid. The predominant menaquinones were identified as MK-9(H6) and MK-9(H8), while the identified polar lipids consisted of aminolipid, diphosphatidylglycerol, glycolipid, hydroxyphosphatidylethanolamine, phospholipid, phosphatidylinositol, phosphatidylethanolamine, phosphatidylglycerol and lipid. The cell wall sugars consist of galactose, glucose and ribose. The predominant cellular fatty acids (>10.0 %) were identified as iso-C15 : 0 (34.8 %) and anteiso-C15 : 0 (14.0 %). Phylogenetic analysis identified that closely related strains for MUSC 164T as Streptomyces javensis NBRC 100777T (99.6 % sequence similarity), Streptomyces yogyakartensis NBRC 100779T (99.6 %) and Streptomyces violaceusniger NBRC 13459T (99.6 %). The DNA–DNA relatedness values between MUSC 164T and closely related type strains ranged from 23.8 ± 0.3 % to 53.1 ± 4.3 %. BOX-PCR fingerprints comparison showed that MUSC 164T exhibits a unique DNA profile, with DNA G + C content determined to be 71.6 mol%. Based on the polyphasic study of MUSC 164T, it is concluded that this strain represents a novel species, for which the name Streptomyces antioxidans sp. nov. is proposed. The type strain is MUSC 164T (=DSM 101523T = MCCC 1K01590T). The extract of MUSC 164T showed potent antioxidative and neuroprotective activities against hydrogen peroxide. The chemical analysis of the extract revealed that the strain produces pyrazines and phenolic-related compounds that could explain for the observed bioactivities.